2015
DOI: 10.1038/sj.bdj.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

A review of dental treatment of head and neck cancer patients, before, during and after radiotherapy: part 1

Abstract: The incidence of head and neck cancer is on the rise. Most head and neck cancers are treated with surgery, radiotherapy, chemotherapy or a combination of these modalities. Patients undergoing radiotherapy can experience several unwanted oral side effects, which have both short and long term implications. Dental general practitioners should be aware of these implications and should liaise closely with the restorative consultants and the oncology team to establish the best oral care pathway. This two-part series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
2
46

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 30 publications
1
91
2
46
Order By: Relevance
“…[5][6][7][8][9] Previous studies demonstrated that head and neck gamma irradiation significantly alters salivary gland structure and function. Particularly, there is loss of parenchymal tissue, acinar atrophy, dilated ducts, and fibrosis in major salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Previous studies demonstrated that head and neck gamma irradiation significantly alters salivary gland structure and function. Particularly, there is loss of parenchymal tissue, acinar atrophy, dilated ducts, and fibrosis in major salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Entre os agudos destacam-se: mucosite, xerostomia, disgeusia, disfagia e infecções secundárias, principalmente candidose e herpes. Dentre os efeitos crônicos estão à cárie de radiação, trismo, fibrose muscular e a osteorradionecrose (JAWAD; HODSON; NIXON, 2015;RADVANSKY;PACE;SIDDIQUI, 2013;SANTOS et al, 2011).…”
Section: Radioterapiaunclassified
“…Dentre os efeitos colaterais e adversos relacionados à RT, destacam-se: a mucosite, que é uma irritação da mucosa oral, que nos estágios iniciais se apresenta eritematosa e dolorida, podendo em graus mais avançados, levar a formação de úlceras (JAWAD; HODSON; NIXON, 2015;RADVANSKY;PACE;SIDDIQUI, 2013). A xerostomia, também muito freqüente, é descrita como -boca seca‖; tem seu inicio geralmente após a segunda semana de tratamento radioterápico, onde as radiações ionizantes provocam alterações nas glândulas salivares, destruição dos ácinos, atrofia e fibrose glandular, tornando a saliva espessa, viscosa e prejudicando seu efeito bactericida (JAWAD; HODSON; NIXON, 2015;DIRIX et al, 2008).…”
Section: Radioterapiaunclassified
See 2 more Smart Citations